Placental expression of eNOS, iNOS and the major protein components of caveolae in women with pre-eclampsia - Smith-Jackson, Kate; Hentschke, Marta; Poli-de-Figueiredo, Carlos; Pinheiro da Costa, Bartira; Broughton Pipkin, Fiona; Czajka, Anna; Mistry, Hiten D. (Elsevier, 2015)
Caveolae regulate many cardiovascular functions and thus could be of interest in relation to pre-eclampsia, a pregnancy specific disorder characterised by hypertension and proteinuria. We examined placental mRNA and protein expression/localisation of the caveolae components Caveolin 1-3, Cavin 1-4 as well as eNOS/ iNOS in normotensive control (n=24) and pre-eclamptic pregnancies (n=19). Placental mRNA expression of caveolin-1, cavin 1-3, was lower and eNOS expression was increased in pre-eclampsia (P<0.05 for all). Additionally Caveolin-1 protein expression was also reduced in pre-eclampsia (P=0.007); this could be an adaptive response in pre-eclampsia, possibly to attenuate the oxidative stress/inflammation.